A 10-year Comparative Study of Organic Carbon Fractions and Carbon Storage in Soils Using Organic and Traditional Soil Management Practices in Rice Farming (Retracted) - Aumtong, Suphathida; Pongwongkam, Paweenoot (Asian Health, Science and Technology Reports, 2018)
The purpose of this study was to investigate and compare the impact of soil management methods applied in both organic rice farming (ORF) and conventional rice farming (CRF) cultivation practices, on the amount of labile organic carbon that can easily be decomposed in the soil, or can be stored as organic carbon in the soil. The participating farmers were divided into two groups: farmers applying organic farming methods (ORF), and those utilizing conventional farming techniques (CRF). Eleven test plots were used in each group, for a total of 22 plots. Each test was replicated 3 times, making 66 physical tests, and each of 22 initial tests replicated 3 times with pseudo replication, giving a total of 99 tests. Carbon fractions analysis in the soil included total organic carbon (TOC) and labile organic carbon fractions (LOC); water soluble carbon (WSC), hot water soluble carbon (HWSC), permanganate oxidized carbon (POXC), carbon in coarse particulate organic matter (CPOM-C) and carbon in fine particulate organic matter (FPOM-C). The results showed that about 82% of the ORF farmers used straw waste from harvesting for fermentation, to cultivate mushrooms and to feed cattle and water buffalo, and both ORF and CRF farmers also burned the rice straw and stubble. In CRF could affect the amount labile organic carbon (LOC). The amount of various fractions of organic carbon that could easily be decomposed, or called labile organic carbon, in both ORF and CRF were analyzed at a soil depth of 0.30 cm. The results showed that the amount of TOC, WSC and HWSC in the ORF soils were much higher than in the CRF soils. Also, the amounts of POXC, CPOM-C and FPOM-C in the CRF soil were higher than in the ORF soil. A further result was that, in CRF soil, labile organic carbon constituted up to about 82% of TOC, while in the ORF soil labile organic carbon constituted only about 35% of TOC. It was also found that all forms of labile organic carbon were higher in CRF soil than in ORF with levels of CPOM-C > FPOM-C >> POXC >> HWSC > WSC. This trend was found in both CRF and ORF soils. We conclude that ORF soil management practices with regard to rice straw usage and crop residue removal affected LOC, and affects the decomposition and mineralization of the soil organic matter available as a plant nutrient. In CRF, the burning of rice straw and crop residue enhanced the amount of LOC.